Strengthening Civic Awareness and Religious Moderation among Millennials Through a Participatory Approach Based on Local Wisdom - Ali Miftakhu Rosyad; Taufik Hidayat; Zaenudin Zaenudin; Affy Khoiriyah; Najeem Olawale Adelakun (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2026)
The increasing cases of intolerance and radicalism among millennials pose a serious threat to Indonesia's diversity and national unity. This community service program aims to strengthen civic awareness and religious moderation through a participatory approach based on local wisdom among millennials in Indramayu Regency. This study employed a one-group pretest-posttest quasi-experimental design with participatory community engagement approach, involving 135 participants consisting of college students, youth members of religious organizations, and community activists aged 18-35 years. The program was implemented through four stages: initial assessment of civic awareness and religious tolerance attitudes, interactive training based on interfaith dialogue, mentoring for implementing religious moderation actions, and evaluation of attitudinal changes. Paired sample t-test analysis (t = 21.35; p < 0.001) revealed statistically significant increases in the civic awareness index from 52.8 to 91.7 (73.8% improvement) and the religious moderation index from 57.4 to 91.5 (68.4% improvement). The program successfully generated 12 religious moderation movements initiated by participants, including interfaith dialogue forums, anti-hoax campaigns on religious content, and collaborative cross-faith social projects. The distinctive contribution of this study lies in the strategic integration of Indramayu's local wisdom ("ngaji bareng" and "silih asih antar umat") as a culturally rooted medium for simultaneously fostering civic awareness and religious moderation, demonstrating that participatory approaches anchored in indigenous values yield more sustainable outcomes than conventional top-down interventions.